LEARNING DESCRIPTIVE WRITING WITH LOCAL TOURISM DESTINATION PICTURES - Firdaus, Firdaus (Tawshiyah: Jurnal Sosial Keagaman dan Pendidikan Islam, 2020)
English is internasional language that used by people in around the world in any levels. So it is studied start form elementary school until college, but they found difficult to study English. Its become a problem for the students or learners  because English is foreign language. Moreover, in our country English is not first or second languge but it is as a foreign language.Teacher should find the batter ways to improve students' English mastery or skill. Making a teaching material, teacher could be do anythings  to improve students' English skill include using a Local Tourism Destination Pictures to improve students English skills especialy in descriptive writing.By using a tool like a picture is make easy for the students to make a hand writing and improve it become a good English writing skill, so using a teaching media like a picture is very effective to improve students’ writing English mastery.